Shift in intelligence issue ownership: conceptualizing CITINT—intelligence conducted by citizens - Pietilä, Iikka; Kortesuo, Katleena; Pohjanen, Ulla; Tuominen, Mikko (Frontiers in Political Science, 2024)
This article elaborates on the conceptualization of CITINT, i.e., the intelligence activities conducted by citizens and NGOs. This article is a preliminary attempt to establish foundation and perspectives for future research and to provide for initial conceptualization of CITINT. Moreover, this article elucidates CITINT’s implications from legislative perspective within the Finnish context. A semi-systematic, limited literature review incorporating academic literature, governmental outlets, and news was executed to explore the contexts and definitions regarding CITINT. Interviews with a journalist, an active CITINT individual, and a detective superintendent of the Finnish National Bureau of Investigation were conducted to clarify and provide backrest for conceptualization. The key contributions of this article are further elucidation of CITINT as a concept and its implications. Moreover, this article discusses the shift in power relations from centralized issue ownership of intelligence activities toward a more fragmented scene in which individuals and non-governmental organizations (NGOs) have more relevance, possibilities, and weight. Within CITINT, this article points out the differentiation between governmentally facilitated CITINT and the bottom-up CITINT conducted by individuals and NGOs on their own terms and tools. One key contribution of this article is connecting CITINT to societal participation through the CCSCM framework. Although the interviews comprise an empirical component, support contextualization, and provide tangible examples, this article’s focus is on the theoretical and conceptual aspects of CITINT. The article concludes with a discussion on the outlook, possibilities, and challenges of CITINT and provokes questions for further discussion on the matter.